2017
DOI: 10.1088/1742-6596/897/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature hydrogen absorption in metallic nanocontacts studied by point-contact spectroscopy measurements

Abstract: Abstract. We report on hydrogen (H) and deuterium (D) atoms absorption below T = 20 K in metallic palladium (Pd) via quantum tunnelling (QT). When a small bias voltage is applied between Pd nanocontacts that are immersed in liquid H2 (D2), the differential conductance spectra measured by point-contact spectroscopy change enormously. The results indicate H (D) absorption in Pd nanocontacts at the temperature where H (D) absorption due to thermal hopping process is not expected, and can be explained by QT. The Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Moreover, it is utilized as a method that can probe the electron density of states (DOS) near the Fermi surface with high resolution [8]. In addition, we found that when a small bias voltage is applied between the metallic palladium (Pd) nanocontacts immersed in liquid H 2 at T < 20 K, the dI/dV spectra show the time evolution from pure Pd to Pd hydride, demonstrating that the H absorption can be advanced by a voltage application to nanocontacts [9,10]. From these results, we considered that in-situ spectroscopic measurements in metal hydrides are possible, because the PCS technique enables to advance H absorption by the voltage application to nanocontacts as well as to trace their dI/dV spectra, which reflect the electronic DOS near the Fermi surface.…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, it is utilized as a method that can probe the electron density of states (DOS) near the Fermi surface with high resolution [8]. In addition, we found that when a small bias voltage is applied between the metallic palladium (Pd) nanocontacts immersed in liquid H 2 at T < 20 K, the dI/dV spectra show the time evolution from pure Pd to Pd hydride, demonstrating that the H absorption can be advanced by a voltage application to nanocontacts [9,10]. From these results, we considered that in-situ spectroscopic measurements in metal hydrides are possible, because the PCS technique enables to advance H absorption by the voltage application to nanocontacts as well as to trace their dI/dV spectra, which reflect the electronic DOS near the Fermi surface.…”
Section: Introductionmentioning
confidence: 93%
“…When applying a bias voltage above the threshold, the spectra evolve significantly, indicating that H absorption proceeds from the surface even at low temperatures owing to the phonon-assisted tunneling induced by the scattering with the ballistic electrons accelerated by the bias voltage. [21][22][23] Consequently, we consider that the interaction of H or D atoms with superconductors can be investigated through spectroscopic measurements. It has been reported that electronic transport through atomicsized metallic junctions in the SC state is affected by H molecules.…”
mentioning
confidence: 99%
“…Note that it is reasonable to consider that H 2 (D 2 ) molecules dissociate into H (D) atoms at the fresh surface exposed to the metallic nanoconstriction because H atoms are absorbed inside metallic nanoconstrictions even at a temperature of approximately 20 K in our previous experiments. [21][22][23] The size of the weak link at the ScS-JJ was adjusted to be optimal for measuring the Josephson current using the MCBJ technique. Subsequently, the contact size was maintained over several dozen hours during the measurements, which was achieved by preventing thermal input in the chamber.…”
mentioning
confidence: 99%
See 1 more Smart Citation